2005
DOI: 10.1159/000088436
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and Loss of Adhesion of Bronchial Epithelial Cells in Asthma

Abstract: Background: Asthma is an inflammatory airway disease associated with infiltration of T cells and eosinophils, increased levels of pro-inflammatory cytokines, and shedding of bronchial epithelial cells (EC). We have recently shown that T cells and eosinophils cooperate in inducing bronchial EC apoptosis in asthma through secretion of IFN-γ and TNF-α. Since EC shedding is a histologic hallmark of asthma, the intercellular junction of EC may be a target of pro-inflammatory cytokines. Methods: Bronchial EC, cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
77
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 55 publications
2
77
0
3
Order By: Relevance
“…Airway epithelial integrity is often compromised in asthma, with detachment of ciliated cells, decreased E-cadherin expression at these sites, disruption of tight junctions and increased permeability to allergens [4][5][6]. Many allergens, including house dust mite (HDM), contain proteolytic activity, causing epithelial damage [7,8].…”
mentioning
confidence: 99%
“…Airway epithelial integrity is often compromised in asthma, with detachment of ciliated cells, decreased E-cadherin expression at these sites, disruption of tight junctions and increased permeability to allergens [4][5][6]. Many allergens, including house dust mite (HDM), contain proteolytic activity, causing epithelial damage [7,8].…”
mentioning
confidence: 99%
“…allergens, to subepithelial layers. Indeed, the airway epithelium is often damaged in asthma, with increased permeability and loss of Ecadherin and ZO-1 expression [2][3][4]. Disruption of the epithelial barrier may also relate to structural abnormalities and epithelial remodelling, i.e.…”
mentioning
confidence: 99%
“…Damage to the epithelium may result in loss of E-cadherin membrane expression and intercellular contacts. It has recently been demonstrated that E-cadherin membrane expression is reduced in bronchial biopsies from asthma patients at the sites of epithelial lesions (24). This may have important consequences, given that E-cadherin is known to negatively regulate multiple signaling pathways.…”
mentioning
confidence: 99%